Remittance Inflows and State-Dependent Monetary Policy Transmission in Developing Countries - Immaculate Machasio; Peter Tillmann (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2017)
Remittance inflows from overseas workers are an important source of foreign funding for developing and emerging economies. This paper estimates nonlinear (smooth-transition) local projections to study the effectiveness of monetary policy under different remittance inflows regimes. We show that for Kenya, Mexico, Colombia and the Philippines monetary policy has a smaller effect under strong inflows of remittances.
Keywords: E52; 330